How to Deduce Human Rights From Natural Law and Other Disciplines - Riofrío Martínez-Villalba, Juan Carlos (Ius Humani. Jornal do direito, 2023)
This research aims to detect the methodologies scholars use to conclude what is a human right or a natural right. For most of them, the mere citation of an article of the constitution or law does not provide enough justification for rights, and they usually resort to other supra-positive elements which are summarized in the " Natural Law Formula". Commonly, they will appeal to human dignity, some psychological or natural inclinations, the values of society, some important goods, goals and means, and to certain principles coined in different places of the legal system. This Article discuss how authors deal with these starting points in their analysis, which precisely are the main elements of the mentioned formula. After showing how the formula works in the human rights field, we consider new possible applications of the versatile formula. It can be used deducing legal conclusions from general principles, ends, values and other elements, and inferring general standards from specific cases, as well. While scholars tend to use the deductive methodology that goes from the general to the particular, courts use the inductive methodology that goes from the case law to the general rules and standards. Finally, the Article introduces new applications of the formula in different sciences and arts related to the human being, like anthropology, ethics, and economics. Thus, this study shows how the formula can be used to develop interdisciplinary studies.